Sodium Levels as a Predicting Factor for the Occurrence of Perforated Appendicitis in Children at Dr. M. Djamil General Hospital Padang - Syukri Alhamda; Jon Efendi; Budi Pratama Arnofyan (HM Publisher, 2022)
Background: Perforation of the appendix can lead to life-threatening complications. Early identification of a perforation before surgery has important clinical implications. Hyponatremia was previously proposed as a marker to differentiate between perforated and non-perforated acute appendicitis. This study aims to determine the role of sodium levels as a predictive factor in the incidence of perforated appendicitis in children at Dr. M. Djamil General Hospital Padang. Methods: This research is an analytic observational study with a cross-sectional design. The research took place from March to May 2022 at Dr. M. Djamil General Hospital Padang. Samples were taken by consecutive sampling with criteria aged 0-18 years and diagnosed with acute appendicitis at Dr. M. Djamil General Hospital Padang. Results: A total of 112 samples with most of the patients (52.7%) aged 6-11 years and found a greater proportion of men (57.1%). Most of the patients underwent laparotomy procedures (57.2%). Hyponatremia was found in 58% of patients. Perforation occurred in most (59.8%) patients. SPSS results showed a significant difference between the incidence of hyponatremia in perforated and non-perforated appendicitis with a p-value <0.001. Conclusion: There is a significant relationship between sodium levels and the incidence of perforation, where the lower the sodium level, the higher the incidence of perforation.